Back pressure effect on three-way catalyst light-off. (September 2019) - Baron, Jan H; Cheng, Wai K
The effect of back pressure on the light-off of a modern spark ignition engine three-way catalyst has been assessed by measuring the hydrocarbon conversion efficiency in a hot flow bench and in the cold-idle period in an engine. In the flow bench experiment, a small amount of propane/air mixture is used as a surrogate for the hydrocarbon mixture. The conversion efficiency is found to be only a function of temperature. The efficiency is independent of pressure, space velocity, and the equivalence ratio of the hydrocarbon mixture for λ ≥ 1. In the engine test, while the engine-out exhaust gas temperature is higher at a higher back pressure, there is little difference between the gas temperatures at the catalyst entrance for different back pressures at retarded spark timing. This observation is attributed to the larger amount of exhaust hydrocarbon conversion oxidation between the engine exit and the catalyst entrance with the lower back pressure. The heat release from this oxidation compensates for the lower engine-out exhaust temperature at the lower back pressure. The catalyst temperature increases modestly and light-off time shortens correspondingly at the higher back pressure. This observation is attributed solely to the increase in mass flow rate (and thus exhaust sensible enthalpy flow rate) of the engine needed to overcome the additional pumping loss due to the throttling of the exhaust. These results have been confirmed with a simple one-dimensional catalyst model.